Jao Tsung-I and Selected Essays on the Cultural Relations History of China and India: An Overview of Siddhartha Studies - Li, Pengling; T’u, Hua-chung; Liu, Hsin-yu (Pacific International Journal, 2025)
Amidst the intensifying global cultural connection, Sino-Indian cultural exchanges have been a crucial domain for comprehending Eastern civilisations, with Jao Tsung-I emerging as a prominent figure in examining their historical profundity and modern relevance. This study focuses on Jao Tsung-I, a distinguished sinologist, and Sino-Indian cultural interactions. This analysis utilises Jao’s scholarly publications, historical documentation, and archaeological evidence to examine his biography, interdisciplinary research, and contributions to Sino-Indian cultural studies, particularly emphasising his book, Essays on the History of Sino-Indian Cultural Relations-Introduction to Siddhartha Studies. The study reveals that Jao’s autonomous learning and cross-cultural viewpoint propelled his success in Sinology, whereas Sino-Indian cultural interactions have developed from ancient Silk Road commerce and the dissemination of Buddhism to contemporary formal and informal collaborations. Jao Tsung-I’s study establishes a theoretical foundation for Sino-Indian cultural studies, and his interdisciplinary approaches serve as a guide for future researchers, enhancing bilateral cultural comprehension and advancing global Sinology.